Description of a new species, Anopheles pseudosundaicus (Diptera: Culicidae) from Kerala, India - Tyagi, B. K.; Hiriyan, J.; Tewari, S. C.; Ayanar, K.; Samuel, P. Philip; Arunachalam, N.; Paramasivan, R.; Krishnamoorthy, R.; Dhananjeyan, K. J.; Leo, S. Victorjerald; Rajendran, R. (Zootaxa, 2009)
Specimens of Anopheles pseudosundaicus, new species, belonging to the Pyretophorus Series of Anopheles (Cellia), were collected from the coastal areas of Alleppey and Kollam districts in Krerala, southwest India. Female (holotype), male (allotype), pupa and fourth-stage larva of this species are described and illustrated to distinguish it from An. subpictus Grassi and An. sundaicus. (Rodenwaldt). It differs from An. sundaicus by the absence of speckling on legs and from An. subpictus in having a complete prehumeral dark spot on costa in wings. A partial sequence of Cytochrome oxidase C subunit 1 (CO1) of mt DNA places An. pseudosundaicus phylogenetically distant from An. sundaicus and closer to An. subpictus.